Nanomonitors: electrical immunoassays for protein biomarker profiling. (August 2008) - Bothara, M; Venkatraman, V; Reddy, R KK; Barrett, T; Carruthers, J; Prasad, S
Aims: The objective of this research is to develop a ''point-of-care'' device for early disease diagnosis through protein biomarker characterization. Here, we present label-free, high sensitivity detection of proteins with the use of electrical immunoassays that we call nanomonitors.Materials & methods: The basis of the detection principle lies in the formation of an electrical double layer and its perturbations caused by proteins trapped in a nanoporous alumina membrane over a microelectrode array platform.Results & discussion: High sensitivity and rapid detection of study protein biomarkers for cardiovascular diseases, C-reactive protein (CRP) and myeloperoxidase (MPO) in pure and clinical samples through label-free electrical detection were achieved. CRP and MPO were detected in pure solutions with a lower detection limit of 200 pg/ml and 500 pg/ml, respectively. These two study proteins were also detected from multiplexed samples containing a mixture of both proteins as well as human serum samples.Conclusions: The performance parameters of the nanomonitors, such as speed of detection on the order of minutes, volume of reagents of a few microliters and low cost per assay are comparable to traditional assay methods, such as ELISA. In addition, nanomonitors also provide the advantages of being a label-free technique with large linear dynamic range of detection and a significant reduction in the size of assay, thus making it an ideal candidate for a clinical diagnostic ''lab-on-a-chip'' device for protein biomarker profiling and hence early disease diagnosis.